A general fluorescent light-up probe for staining and quantifying protein. Issue 8 (28th August 2019) - Zou, Jiawei; Chen, Gangyi; Du, Feng; Yuan, Yi; Huang, Xin; Dong, Juan; Xie, Kexin; Cui, Xin; Tang, Zhuo
Abstract : Proteins are the primary functional agents in all cellular processes, facilitating various functions such as enzymes and structure-forming or signal-transducing molecules. In this work, we report a fluorescent dye, PyMDI-Zn, which could specifically bind with proteins and provide a red-shifted fluorescent emission. The visual analysis of protein in sodium dodecyl sulfate-polyacrylamide gel electrophoresis could be realized in 5 min by using PyMDI-Zn as a light-up dye. Based on its cell penetration and low toxicity, PyMDI-Zn could also be applied to locate protein-rich regions and organelles in live cell imaging. Moreover, the direct protein quantitation can be realized based on PyMDI-Zn, providing a method of screening for food adulteration by nitrogen-rich compounds.